ENGKLEK SEBAGAI SARANA PEMBELAJARAN YANG ASIK DI TENGAH PERMAINAN MODERN - Pebryawan, Krisna (MAGISTRA, 2015)
Abstract : Engklek game is a type of traditional childrenâs games are quite popular in his time. engklek become the most widely played game, the many variants, both the name and form. In this paper we study about the importance of maintaining engklek game in the middle of the rapids game paced modern luxury. Engklek game is not meant to get rid of the modern game, not antipathy to the modern game. The game is intended as a counterweight engklek between the modern game and traditional games. The analysis in this paper includes the values contained in the game engklek seen from the pattern drawing and playing techniques. The expected result is the kids have fun in the play engklek especially able to absorb the values contained in the game engklek like sportivity, hard work, creativity, and sense of community